Design and Development of Web-Based Cooperative Financial Applications at SMP Negeri 7 Prabumulih - Prederika Tri Pebiyolanda; Andi Christian; Nurmayanti (Jurnal Teknologi Informatika dan Komputer, 2026)
The school cooperative is one of the supporting facilities for students' economic activities that plays an important role in providing school supplies and training students' independence and responsibility. The space is usually used by students to conduct transactions between students and cooperative officers. Currently, the cooperative of SMP Negeri 7 Prabumulih serves students in recording goods purchase transactions still using a conventional system. The method of inputting financial reports at this institution has used Microsoft Excel for monthly reports and manual recording in books, but the system used is still manual. This condition has the potential to cause various problems, such as delays in preparing reports, recording errors, and ineffective archiving of financial data. The purpose of this study is to create a Web-based Application to facilitate the Cooperative of SMP Negeri 7 Prabumulih in inputting financial reports, processing, and presenting financial data in a structured and systematic manner. The research method used in this study is a qualitative descriptive method with data collection in the form of observation, interviews and literature studies. The type of data used is qualitative data and data sources consist of primary and secondary data. System development is carried out using a prototype method to be able to adjust to user needs gradually. This web-based application uses the PHP programming language, a MySQL database, and PDF formats for reporting. Research shows that the application can improve the efficiency of cooperative financial management, minimize recording errors, and facilitate management in producing accurate and timely financial reports.